Accelerated versus standard corneal collagen crosslinking combined with same day phototherapeutic keratectomy and single intrastromal ring segment implantation for keratoconus. Issue 2 (19th August 2014) - Elbaz, Uri; Shen, Carl; Lichtinger, Alejandro; Zauberman, Noa Avni; Goldich, Yakov; Ziai, Setareh; Rootman, David S
Abstract : Aim: To compare the results of same day transepithelial phototherapeutic keratectomy (t-PTK) and single inferior intracorneal ring segment (ICRS) combined with standard versus accelerated corneal collagen crosslinking (CXL) for keratoconus. Methods: All consecutive progressive keratoconus eyes that underwent standard or accelerated CXL treatment preceded by same day t-PTK and placement of a single inferior ICRS and had 6 and 12 months of follow-up were reviewed retrospectively. Eyes were classified into two groups, the 'standard' and the 'accelerated' group, accordingly. Visual, refractive and topographic data prior to surgery and at 6 and 12 months post-treatment were analysed. Results: Sixteen eyes were included in each of the standard and the accelerated groups. Mean patient age was 27.5±8.5 years and 30.5±10.7 years (p=0.38) in the standard and accelerated groups, respectively. There was a significant improvement in uncorrected distance visual acuity, refractive cylinder and all examined corneal parameters in both groups 12 months postsurgery. The corrected distance visual acuity and manifest refraction spherical equivalent showed a significant improvement after 12 months of follow-up only in the accelerated group. However, mean changes in all evaluated parameters did not differ significantly between the two groups. Conclusions: A combined treatment of accelerated CXL preceded by same day t-PTK and single ICRS is as effective as the combined treatment using standard CXL for visual rehabilitation in progressive keratoconus.